PENGARUH INFLASI, NILAI TUKAR, PRODUK DOMESTIK BRUTO DAN BI RATE TERHADAP KINERJA SAHAM (Studi Pada Perusahaan Sektor Property dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022) - Halimah, Siti; Rosmini Ramli (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The purpose of this study was to determine how macroeconomic factors, namely inflation, exchange rates, gross domestic product and bi rates, affect stock performance with the Property and Real Estate Sector companies on the Indonesia Stock Exchange. The objects in this study are 23 companies in the Property and Real Estate Sector for 5 years on a quarterly basis in the 2018-2022 period with data collection techniques, namely purposive sampling so as to obtain a sample of 460 data. The method used in testing data is panel regression analysis. The result of this test is that inflation has a significant positive effect due to the inflation data used in the analysis, which covers a research period that does not exceed 10%. Other independent variables such as exchange rate, gross domestic product and bi rate have no significant impact on stock performance.